Optimism with Coping Stress in Nomads College Students - Puspa Setyaningrum Weny; M. Dinah Charlota Lerik; M. K. P. Abdi Keraf (Journal of Health and Behavioral Science, 2022)
Nomads students as foreigners from different environments are required to be able to adapt to their new environment, which can be a source of stress. Individuals who experience stress will be encouraged to do coping. Individuals who have an optimistic attitude tend to see problems as natural and can solve their problems. The purpose of this study was to determine the relationship between optimism and coping stress in nomad students of The Primary School Teacher Education Department of the University of Muhammadiyah Kupang. The sampling technique used convenience sampling with a total sample of 92 people. Data analysis in this study used Pearson product-moment correlation analysis. The result got 0,238 and p = 0,022 indicates that there is a positive relationship between optimism and coping stress in nomad students in The Primary School Teacher Education Department of the University of Muhammadiyah Kupang.